Planimetry as a Structural Component of Structure for Professional Training of a Future Teacher of Mathematics - Bozorov Zokir Yuldosh oglu; Khabibulloyev Abbos Odil oglu; Turakhanov Jakhongir Utkir oglu; Otaganova Umida Egamberdi qizi (International Journal on Integrated Education, 2022)
In this article, the essence and component composition of the competence of the future teacher in the field of planimetry and its teaching methods are defined as one of the components of his professional competence.